2015
DOI: 10.1159/000440626
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience Performing Percutaneous Ultrasound Examination with Real-Time Virtual Sonography with Color Display

Abstract: Purpose: We report the efficacy of percutaneous ultrasound (US) examination using a novel real-time virtual sonography (RVS) method that collates multiple Digital Imaging and Communications in Medicine (DICOM) data sources and displays reference images in color. Materials and Methods: A total of 7 patients with 9 hepatocellular carcinomas were evaluated. Using the SYNAPSE VINCENT volume analyzer, DICOM data of the portal vein, hepatic vein, tumor, and hepatic segment were isolated from contrast-enhanced comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One of the famous applications of SYNAPSE 3D, liver analysis, was originally developed for the simulation of the resection range for hepatectomy [30], and usefulness of the clinical application of the virtual ultrasound software included in liver analysis has also been indicated [31]. And using this software, we can perform colorized fusion system in colored display on the US monitor [32]. There are 2 types of SYNAPSE 3D systems.…”
Section: Discussionmentioning
confidence: 99%
“…One of the famous applications of SYNAPSE 3D, liver analysis, was originally developed for the simulation of the resection range for hepatectomy [30], and usefulness of the clinical application of the virtual ultrasound software included in liver analysis has also been indicated [31]. And using this software, we can perform colorized fusion system in colored display on the US monitor [32]. There are 2 types of SYNAPSE 3D systems.…”
Section: Discussionmentioning
confidence: 99%
“…Software-assisted planning and simulations are also beneficial for percutaneous ablation. Graphics software (including Advantage Workstation ® (GE Healthcare; Waukesha, WI, USA), SYNAPSE VINCENT ® (Fujifilm Medical; Tokyo, Japan), Ziostation2 ® (Ziosoft Inc.; Tokyo, Japan), AZE Virtual Place ® (Canon Medical; Tokyo, Japan), and BioTrace IO ® (TechsoMed; Rehovot, Israel)) display the following scenarios: a pre-interventional simulation, including the orientation and positioning of a tumor and the optimization of access paths, and a peri-interventional simulation, including predictions of the ablation zone and thermal organ injury [18,19].…”
Section: Planning Us and Software-based Planningmentioning
confidence: 99%
“…Ogawa et al [7] reported the efficacy of percutaneous ultrasound (US) examination using a novel, real-time virtual sonography method that collates multiple Digital Imaging and Communications in Medicine (DICOM) data sources and displays reference images in color. They concluded that real-time virtual sonography with color display demonstrates utility in increasing operator comprehension of spatial and positional relationships during percutaneous US examination.…”
Section: Tablementioning
confidence: 99%